Grape byproduct flour: perceptions in the juice and wine industries about residue destination - Carlini, Nataly Roberta Bezerra Santana; Bulhões, Flavia Muradas; Sant Anna, Voltaire (Cadernos de Ciência & Tecnologia, 2024)
Grape pomace flour, an important functional ingredient, is rarely found in the market and there is no known data in the literature to evaluate the reasons why. Therefore, the objective of this work was to analyze the perception of entrepreneurs and technicians regarding the transformation of grape pomace into products for human consumption and to evaluate the current destination given to this residue. The research was qualitative and was carried out from 2019 to 2020 through in-depth interviews with nine key informants from companies located in the Vale dos Vinhedos region, in Southern Brazil. The results showed that few companies produce flour/powders and seed oil from grape pomace, and that most of them destinate the residue for composting and animal feed. Moreover, the results show that grape pomace flour is perceived as a great potential raw material to develop new products for human consumption, but that the main obstacles for this use were the company’s focus on beverage production, a lack of knowledge of specific technologies for this type of production, the large investments required for this new production chain, reduced labor in family-farming companies, and market uncertainties. Additionally, the concern of the companies to comply with environmental legislation was a strong motivator for the destination of the generated grape pomace. The present work brings important information for the grape-producing chain and the scientific community to evaluate the destination of the generated residues, aiming for the adoption of an ecoinnovative approach to grape pomace.